1998
DOI: 10.1021/jm970179x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of Carboxyflavones as Structurally Rigid CysLT1 (LTD4) Receptor Antagonists

Abstract: The synthesis and CysLT1 receptor affinities of a new series of highly rigid 3'- and 4'-(2-quinolinylmethoxy)- or 3'- and 4'-[2-(2-quinolinyl)ethenyl]-substituted, 6-, 7-, or 8-carboxylated flavones are described. CysLT1 receptor affinities of the flavones (down to 11 nM) were determined by their ability to displace [3H]LTD4 from its receptor in guinea pig lung membranes. Structure-affinity relationship studies showed that the relative positions of the carboxylic acid and the quinoline moiety were critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…For the properties and biological activity of quinoline derivatives, see: Vaitilingam et al (2004); Lee et al (2004); Zwaagstra et al (1998); Roma et al (2000); Ferrarini et al (2000). For the preparation of quinoline derivatives, see: Zhou et al (2010); Yang et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…For the properties and biological activity of quinoline derivatives, see: Vaitilingam et al (2004); Lee et al (2004); Zwaagstra et al (1998); Roma et al (2000); Ferrarini et al (2000). For the preparation of quinoline derivatives, see: Zhou et al (2010); Yang et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…4) for the leukotriene agonists/antagonists, namely, (1) a lipophilic anchor (side chain), (2) a central flat unit (triene), (3) an ionic pocket (peptide and/or carboxylic acid group), and (4) a hydrophilic site (acidic group). Since this description, other workers have further refined this conceptual model to a three-dimensional one [44,45,46,47]. Interestingly, the three-dimensional models have suggested that all CysLT 1 antagonists may not bind to the same site or in the same manner as the endogenous ligand.…”
Section: Eicosanoid Ligand Modificationsmentioning
confidence: 99%
“…19 The main known synthetic methods for obtaining flavones are oxidative cyclization of 2′-hydroxychalcones, 20 the cyclodehydration of 1-(2-hydroxyphenyl)-3-phenyl-1,3-propanedione 21 and via an intermolecular Wittig reaction. 22 Reagents that have been used for the oxidation of 2′-hydroxychalcones and flavanones to obtain flavones are SeO 2 -pentan-1-ol, 20 Pd-C/vacuum, 22 I 2 -DMSO, 23 SeO 2 -DMSO, 24 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ)-dioxane, 25 NaIO 4 --DMSO, 26 nickel peroxide-dioxane, 27 H 2 O 2 -NaOH, 28 Dowex H + -2-propanol, 23a,29 SeO 2 -dioxane, 30 SeO 2 -3-methyl-1-butanol (isoamyl alcohol), 31 Br 2 --NaOH, 32 Tl(NO 3 ) 3 ·3H 2 O 33 and I 2 -triethylene glycol. 34 Most of these methods are of limited use as they suffer from low yields and often afford a mixture of products containing flavones, flavanones and aurones.…”
Section: Introductionmentioning
confidence: 99%